Agribusiness Development Model in Sharia-Based Socio-Economic Planning for Community Welfare in Pakarhumbada Regency - Muller Tamba; Chuzaimah Batubara; Isnaini Harahap (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Background: The agricultural sector, particularly in rural areas like Pakarhumbada in North Sumatra, plays a crucial role in Indonesia's economy. However, despite its potential, the sector faces significant challenges, including low farmer welfare, weak infrastructure, and limited access to modern agricultural practices. This research aims to analyze the development model of agribusiness in Pakarhumbada based on Islamic economics, specifically integrating the principles of maqāṣid al-syarī‘ah to improve farmer welfare. Method: The study employs a qualitative approach combined with path analysis to explore the impact of production inputs, agricultural practices, market systems, and supporting factors on both the implementation of Islamic economics and the welfare of farmers. Results: The novelty of this research lies in the application of Islamic economic principles, including musyarakah, mudharabah, and wakaf within an agribusiness context, addressing the structural challenges that have hindered optimal agricultural growth. The study's findings indicate that enhancing the agricultural sector's value chain, improving farmer access to finance, and incorporating local Islamic economic practices can significantly improve economic stability for farmers. The future impact of these findings could reshape agribusiness practices in rural Indonesia, creating a more inclusive and sustainable economic environment for smallholder farmers Conclusion: The implications of this research suggest that for the agribusiness sector to thrive in regions like Pakarhumbada, policies must incorporate a more holistic approach that integrates Islamic economic practices, strengthens local institutions, and provides equitable access to resources. This framework could serve as a model for other agrarian regions in Indonesia, enhancing both economic and social welfare